UNaProd: A Universal Natural Product Database for Materia Medica of Iranian Traditional Medicine. (13th May 2020) - Naghizadeh, Ayeh; Hamzeheian, Donya; Akbari, Shaghayegh; Mohammadi, Fahimeh; Otoufat, Tohid; Asgari, Saeme; Zarei, Azadeh; Noroozi, Samane; Nasiri, Najmeh; Salamat, Mahdi; Karbalaei, Reza; Mirzaie, Mehdi; et al.
Abstract : Background . Iranian traditional medicine (ITM) is a holistic medical system that uses a wide range of medicinal substances to treat disease. Reorganization and standardization of the data on ITM concepts is a necessity for optimal use of this rich source. In an initial step towards this goal, we created a database of ITM materia medica . Main Body . Primarily based on Makhzan al-Advieh, which is the most recent encyclopedia of materia medica in ITM with the largest number of monographs, a database of natural medicinal substances was created using both text mining methods and manual editing. UNaProd, a Universal Natural Product database for materia medica of ITM, is currently host to 2696 monographs, from herbal to animal to mineral compounds in 16 diverse attributes such as origin and scientific name. Currently, systems biology, and more precisely systems medicine and pharmacology, can be an aid in providing rationalizations for many traditional medicines and elucidating a great deal of knowledge they can offer to guide future research in medicine. Conclusions . A database of materia medica is a stepping stone in creating a systems pharmacology platform of ITM that encompasses the relationships between the drugs, their targets, and diseases. UNaProd is hyperlinked to IrGO and CMAUP databases for Mizaj and molecular features, respectively, and it is freely available at http://jafarilab.com/unaprod/ .